Studenti svantaggiati e fattori di promozione della resilienza - Fabio Alivernini; Sara Manganelli; Fabio Lucidi; Ines Di Leo; Elisa Cavicchiolo (LED Edizioni Universitarie, 2017)
Many studies showed the impact that the socio-economic context and students' characteristics, such as gender and migratory background, have on mathematical performance. This situation poses a problem of equity of the educational system: some groups of young people are in fact disadvantaged for reasons independent of their commitment to the study. The aim of this paper is to evaluate the presence of factors on which teachers can intervene, allowing disadvantaged students to achieve excellence. The contribution aims to identify associated factors not only to compensate for the disadvantage associated with student background conditions, but to a real reversal of predictions in terms of skills acquired. The results show the impact that geographic membership, the socio-economic-cultural background of schools and families and gender, in their interaction, exert in defining situations of major disadvantage for students. At the same time, there is evidence for the protective role played by some teaching strategies, student self-beliefs, and other factors related to specific background situations.